Adverse respiratory outcome after premature rupture of membranes before viability. (19th December 2013) - Verspyck, Eric; Bisson, Violene; Roman, Horace; Marret, Stéphane
Abstract Aim To determine whether preterm premature rupture of membranes (PPROM) before 24 weeks is an independent risk factor for poor outcome in preterm neonates. Methods A retrospective comparative cohort study was conducted, including viable premature infants born between 25 and 34‐weeks gestation. Each preterm case with early PPROM was matched with two preterm controls of the same gestational age at birth, sex and birth date and who were born spontaneously with intact membranes. Logistic regression was performed to identify independent risk factors associated with composite respiratory and perinatal adverse outcomes for the overall population of preterm infants. Results Thirty‐five PPROM cases were matched with 70 controls. Extreme prematurity (26–28 weeks) was an independent risk factor for composite perinatal adverse outcomes [odds ratio (OR) 43.9; p = 0.001]. Extreme prematurity (OR 42.9; p = 0.001), PPROM (OR 7.1; p = 0.01), male infant (OR 5.2; p = 0.02) and intrauterine growth restriction (IUGR, OR 4.8; p = 0.04) were factors for composite respiratory adverse outcomes. Conclusion Preterm premature rupture of membranes before viability represents an independent risk factor for composite respiratory adverse outcomes in preterm neonates. Extreme prematurity may represent the main risk factor for both composite respiratory and perinatal adverse outcomes.